Transatlantic Trade and Investment Partnership (TTIP): Impact and correlation analysis based on trade and investment between Turkey and EU, and the USA - Betül Yüce Dural; S. M. Rashed Jahangir (Journal of Contemporary Economic and Business Issues, 2018)
The main objective of this study is to ascertain the importance and necessity of Turkey, based on trade and investment, in TTIP agreement as a partner country with both European Union (EU) and the USA. Here, it uses secondary data sources - Central Bank of the Republic of Turkey (CBRT) and Turkish Statistical Institute - from 2001 to 2016. To obtain vibrant findings, the study introduces two statistical analyses: correlation and regression. In addition, it elucidates descriptive analysis for comprehending the general trade and investment scenario. The results derived from correlation suggest that there is a strong positive correlation between Turkey's total foreign trade and its export to and import from EU and the USA, Turkey's total FDI and EU's FDI in Turkey, as well as Turkey's total FDI and the USA's FDI in Turkey. In addition, a strong positive correlation has been found between Turkey's total resident FDI in abroad and Turkey's FDI in EU and the USA. On the other hand, the regression results indicate that Turkey's trade and investment with EU and the USA have a significant impact on Turkey's total foreign trade and investment.
Keywords: F14; F21; 330; TTIP; Turkey; European Union; the USA; Customs Union; PTA